2001
DOI: 10.1074/jbc.m009774200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Transsulfuration and Cysteine Biosynthetic Pathways in the Protozoan Hemoflagellate, Trypanosoma cruzi

Abstract: Sulfur-containing amino acids play an important role in a variety of cellular functions such as protein synthesis, methylation, and polyamine and glutathione synthesis. We cloned and characterized cDNA encoding cystathionine ␤-synthase (CBS), which is a key enzyme of transsulfuration pathway, from a hemoflagellate protozoan parasite Trypanosoma cruzi. T. cruzi CBS, unlike mammalian CBS, lacks the regulatory carboxyl terminus, does not contain heme, and is not activated by S-adenosylmethionine. T. cruzi CBS mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 56 publications
(37 reference statements)
3
68
1
Order By: Relevance
“…Recently, work from another group has suggested that the formation of CBS tetramers may involve residues outside of the C-terminal domain (20). The series of deletion mutants generated in this present study provides us with a useful tool to further delineate the one or more regions of CBS associated with the formation of tetramers.…”
Section: Effect Of Truncations On the Oligomeric Status Of Cbs-mentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, work from another group has suggested that the formation of CBS tetramers may involve residues outside of the C-terminal domain (20). The series of deletion mutants generated in this present study provides us with a useful tool to further delineate the one or more regions of CBS associated with the formation of tetramers.…”
Section: Effect Of Truncations On the Oligomeric Status Of Cbs-mentioning
confidence: 92%
“…The function of this ligand is unknown, but a number of studies indicate it may play either a regulatory or structural role (13)(14)(15)(16). The observation that both yeast (17)(18)(19) and Trypanosoma cruzi (20) CBS lack heme indicates that it is not directly involved in catalysis (18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that LmajMST works in conjunction with both recombinant L. major cysteine synthase (GenBank TM accession number AL499624) and recombinant L. major cystathionine ␤-synthase (accession number AL499619) to synthesize cysteine in vitro. T. cruzi cystathionine ␤-synthase was also recently reported to possess cysteine synthase activity (45).…”
Section: Figmentioning
confidence: 99%
“…An evolutionary relationship between these enzymes is also illustrated by the fact that some CBS enzymes have retained CS activity [4]. CS and CBS, together with other enzymes such as β-cyanoalanine synthase, the β-subunit of tryptophan synthase and cysteine lyase, catalyze primarily β-replacement reactions [5,6].…”
mentioning
confidence: 99%